R & D Investment in Oligopoly: Betrand vs Cournot - Flavio Delbono; Vincenzo Denicolò (Alma Mater Studiorum - Università di Bologna, Dipartimento di Scienze Economiche (DSE), 1988)
Since the work of Schumpeter, it has been argued that there may exist a trade-off between static and dynamic efficiency. As a contribution to this debate, in this paper we compare the R&D performance of CCournot and Bertrand oligopolists. We model a one-shot noncooperative game in which firms invest in R&D, with the aim of being first in a competition for a patentable cost-reducing innovation.
Keywords: 330